Ambivalent and Contradictory: Victorian Architects’ Responses to Technology - Richard W. Hayes (Cahiers Victoriens et Edouardiens)
Victorian architecture was riven with contradictions. Technophilia and technophobia commingled in British architectural culture of the second half of the nineteenth century. On the one hand, architects and engineers gave shape to buildings that employed the most up-to-date materials and processes made available by modern technology such as iron and glass, prefabrication, and machine-made goods. On the other hand, some of the strongest condemnations of industrialism were voiced from within architectural culture. Both Augustus Welby Northmore Pugin and John Ruskin saw architecture as the optimal site from which to mount vigorous critiques of the modern world as they idealized the Middle Ages in order to denounce the social ills concomitant with industrialism. How did individual Victorian architects square such critiques with the need to build for real-world clients in the here and now of the nineteenth century? This essay unpacks the contradictions in Victorian architecture by focusing on the ways in which George Gilbert Scott and E. W. Godwin navigated the competing demands of modern technology and an idealized historical past in their practices. Scott’s design for the Midland Grand Hotel at St. Pancras embodies the contradiction between up-to-date engineering and an architecture predicated on revivalism. Godwin, by contrast, adopted an ambivalent attitude toward revivalism as he speculated on the possibility of a simple, style-less way of building that accepted the realities of contemporary life. Taken together, Scott and Godwin’s careers exemplify complex and unresolved responses to the advantages and disadvantages of their technological moment.